What causes it? Impulsive buying among generation Z on Shopee : Qualitative Study of Generation Z Consumer Behavior in Surabaya in the Digital Era - Kholid, Ikhwan (Publisher Cv. Inara, 2025)
This research aims to identify the factors influencing impulsive shopping behaviour on the e-commerce platform Shopee among Generation Z in Surabaya. With the increasing use of digital technology and the internet, consumer behaviour has undergone significant changes, particularly among the younger generation. Employing a qualitative approach, this study collected data through in-depth interviews with respondents who are active Shopee users in Surabaya. The findings indicate that factors such as promotions, shopping experiences, social media influences, and platform design significantly contribute to the impulsive behaviour of Generation Z. These findings provide critical insights for marketers in designing more effective marketing strategies.